1991
DOI: 10.1002/smj.4250120203
|View full text |Cite
|
Sign up to set email alerts
|

Output flexibility—A competitive advantage for small firms

Abstract: We explore three theoretical perspectives that look at output flexibility as a competitive udvantage for small firms as was initially described by Stigler (1939). First, small firms are more willing to fluctuate their output. As a result: second, small firms can trade cost ineficiency with volume flexibility to increase their profits; third, output flexibility is u more viable source of competitive udvantage in rvolatile und capital-intensive industries, and less viable in profitable industries. Indeed, the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
221
2
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(242 citation statements)
references
References 20 publications
12
221
2
7
Order By: Relevance
“…Larger firms are more likely to have formalized routines, policies, and structures in place that impede implementation of HRM practices. In fact, smaller firms have been found to be more flexible (Fiegenbaum & Karnani, 1991;Levy & Powell, 1998) and experience less inertia (Hannan & Freeman, 1984) than larger firms. Further supporting our notion, Garrison (2009) found that organization size impeded organizational response capability on the early adoption of disruptive technology, with larger firms having fewer early adoptions.…”
Section: The Moderating Role Of Firm Sizementioning
confidence: 99%
“…Larger firms are more likely to have formalized routines, policies, and structures in place that impede implementation of HRM practices. In fact, smaller firms have been found to be more flexible (Fiegenbaum & Karnani, 1991;Levy & Powell, 1998) and experience less inertia (Hannan & Freeman, 1984) than larger firms. Further supporting our notion, Garrison (2009) found that organization size impeded organizational response capability on the early adoption of disruptive technology, with larger firms having fewer early adoptions.…”
Section: The Moderating Role Of Firm Sizementioning
confidence: 99%
“…Sethi and Sethi (1990), expanding on B rowne's (1984) proposition, suggestthat volumeflexibility could be measured by the range of volumes in which the firm can run profitably. Fiegenbaum and Karnani (1991) actually measure volume flexibility as the standard deviation of annual sales. They focus on studying the relationship between volume flexibility, firm size, and profitability using aggregate data from the COMPUSTAT database.…”
Section: Flexibility Measurementmentioning
confidence: 99%
“…The second group deals with the relationship between flexibility and performance, and includes a few studies that present data to support their claims. Examples are Jaikumar (1986), Tombak (1988), Tombak and de Meyer (1988), and Fiegenbaum and Karnani (1991). The third group deals with historical and economic analyses of flexibility, and tends to view flexibility as an attribute of importance for the competitiveness of a firm, industry, or country.…”
Section: Introduction'mentioning
confidence: 99%
“…Hall and Weiss [29] found a positive relation between firm size and profitability for Fortune 500 firms. Similarly, study by Fiegenbaum and Karnani [30] found a positive relation between firm size and profitability. As no previous studies were dedicated to studying the impact of capital structure determinants of information technology companies in Bangladesh, this paper explores this spectrum.…”
Section: Literature Reviewmentioning
confidence: 75%